2014
DOI: 10.1039/c3cp53636j
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism behind the stabilization of multi-charged metal cations in water: a case study of the electronic states of microhydrated Mg2+, Ca2+ and Al3+

Abstract: Metal atoms typically have second and higher ionization potentials (IPs) that are larger than the IP of water, resulting in the Coulombic explosion of the first few [M(H2O)n](+q) (q≥ 2) gas phase clusters as the M(+(q-1)) + (H2O)n(+) or MOH(+(q-1)) + H3O(+)(H2O)n-2 energy levels are energetically more stable than the M(q+) + (H2O)n ones for small n. We present a theoretical analysis of the various electronic states arising from the sequential hydration of the Ca(2+), Mg(2+) and Al(3+) cations with up to six wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Recently, we have studied the interaction of the Mg 2+ , Ca 2+ , and Al 3+ ions with up to six water molecules 64 with the water ligands approaching the metal centers along the same path as the one used in this study. We showed that the ground state hexa-aqua metal equilibrium structure originates from the Mg 2+ /Ca 2+ /Al 3+ + nH 2 O fragments and that these multivalent ions can be stabilized in an aqueous environment with respect to the water ionization channel only if the number of the water molecules in their first solvation shell is larger than a critical number n, which is 0, 1, and 4 for calcium, magnesium, and aluminum, respectively.…”
Section: Iron−water Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have studied the interaction of the Mg 2+ , Ca 2+ , and Al 3+ ions with up to six water molecules 64 with the water ligands approaching the metal centers along the same path as the one used in this study. We showed that the ground state hexa-aqua metal equilibrium structure originates from the Mg 2+ /Ca 2+ /Al 3+ + nH 2 O fragments and that these multivalent ions can be stabilized in an aqueous environment with respect to the water ionization channel only if the number of the water molecules in their first solvation shell is larger than a critical number n, which is 0, 1, and 4 for calcium, magnesium, and aluminum, respectively.…”
Section: Iron−water Interactionmentioning
confidence: 99%
“…In this case, the Coulombic repulsion vanishes while the charge−dipole interaction is enhanced since now iron is doubly charged. Considering only the electrostatic interactions and the IE 2 = IE(Fe + → Fe 2+ ) and IE W = IE(H 2 O → H 2 O + ) ionization energies, we can estimate the distance R* for which the PECs from the first and third adiabatic channels under consideration cross by 64 μ μ…”
Section: Iron−water Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvation of metal cations by water underlies many important chemical systems, such as electrochemical reactions, acid–base chemistry, atmospheric aerosols, and the many aqueous biochemical processes that govern life itself. The molecular details of cation–water interactions have been investigated with many studies of the mass spectrometry of gas-phase ion–molecule complexes and with corresponding computational studies. Collision-induced dissociation measurements have determined cation–water binding energies, while computational studies have provided structures, relative energetics, and predicted spectra for complexes with different numbers of water molecules and different charge states. Spectroscopic experiments in either the UV–visible or infrared regions have determined the structures and the coordination numbers of different metal ions interacting with water. In the present report, we use mass spectrometry and infrared photodissociat...…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of electrons and charges (cations) would increase the cumulative Cs. Electrolytes containing multiple oxidation state metals have been investigated intensively to yield a highcapacity battery [82,83]. A similar concept could be adopted in the screening of transition metals for PC electrode with high Cs.…”
mentioning
confidence: 99%